Presidential conflict in Côte d'Ivoire : governance, political power, and social justice - Okosun, T. Y. (Lexington Books, 2018)
This book examines democracy, governance, and social justice in Côte d'Ivoire by analyzing the political effects of the 2011-2012 presidential conflict. Okosun explains driving factors that caused this conflict through an examination of the social and historical context surrounding the political battle between Laurent Gbagbo and Alassane Ouattara.